Antibacterial high-strength toilet ceramic material and method for manufacturing the same

CN122940437APending Publication Date: 2026-10-20GUANGDONG TAINI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611091052.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]马桶陶瓷需具备足够力学强度以保证使用寿命,但目前产品多存在抗菌与强度难以兼顾的问题:表面涂覆抗菌涂层易脱落、抗菌时效短;添加单一银系、锌系抗菌剂耐热性差,高温烧结易失活,抗菌谱窄且可能存在重金属溶出风险

Benefits of technology

本发明的一种抗菌高强度马桶陶瓷材料及其制备方法,通过将高岭土、石英、长石、复合改性纳米氧化铝、微米碳化硅、改性膨润土以及抗菌剂放入球磨机并加去离子水球磨,经真空练泥后注浆成型,干燥后得到干燥坯体,将长石、石英、高岭土、碳酸钙、抗菌剂以及烧结助剂放入球磨机并加去离子水球磨,静置后得到釉料浆料,之后对干燥坯体喷釉晾干,经低温素烧、高温烧结及冷却,得到抗菌高强度马桶陶瓷材料;该抗菌剂可使马桶陶瓷在高温烧结后仍具备高效、广谱、持久抗菌性能,且与陶瓷基体相容性好、耐高温、不影响材料强度与釉面质量,真正实现抗菌与高强度一体化;复合改性纳米氧化铝可显著提升马桶陶瓷的致密度、抗弯强度与硬度,同时在坯体中分散均匀、不影响抗菌剂活性,实现高强度与高效抗菌协同兼容;改性膨润土可提升马桶陶瓷坯体的可塑性、干坯强度与成型稳定性,减少干燥开裂,同时助力抗菌离子均匀分散,不影响陶瓷高温烧结性能与抗菌效果,兼顾成型加工性、高强度与抗菌持久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784703677390-000001
    Figure REF-OBJ-1784703677390-000001
Patent Text Reader

Abstract

This invention relates to the field of toilet ceramic materials, specifically to an antibacterial high-strength toilet ceramic material and its preparation method, solving the problems of unstable antibacterial properties, high-temperature deactivation, and insufficient strength in traditional toilet ceramics. The method involves placing kaolin, quartz, feldspar, composite modified nano-alumina, micron-sized silicon carbide, modified bentonite, and an antibacterial agent into a ball mill with deionized water for ball milling. After vacuum kneading, the mixture is poured into a slurry and dried to obtain a dry green body. Feldspar, quartz, kaolin, calcium carbonate, the antibacterial agent, and a sintering aid are then placed into a ball mill with deionized water for ball milling. After settling, a glaze slurry is obtained. The dried green body is then sprayed with glaze and dried. Following low-temperature bisque firing, high-temperature sintering, and cooling, the antibacterial high-strength toilet ceramic material is obtained. This antibacterial high-strength toilet ceramic material possesses excellent and efficient antibacterial properties, high strength, stable molding performance, and excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of toilet ceramic materials, specifically to an antibacterial high-strength toilet ceramic material and its preparation method. Background Technology

[0002] With the increasing awareness of hygiene and health, the antibacterial properties and mechanical strength of toilet ceramics have attracted much attention. Since they are in a dark and humid environment for a long time, they are prone to the growth of pathogenic bacteria and pose health risks. Therefore, giving them efficient and long-lasting antibacterial properties has become an industry trend.

[0003] Toilet ceramics need to have sufficient mechanical strength to ensure service life, but current products often have the problem of not being able to balance antibacterial properties and strength: the antibacterial coating on the surface is easy to fall off and the antibacterial effect is short-lived; the addition of single silver-based and zinc-based antibacterial agents has poor heat resistance, is easy to deactivate at high temperature sintering, has a narrow antibacterial spectrum and may pose a risk of heavy metal leaching.

[0004] Ordinary unmodified nano-alumina is prone to agglomeration and has poor compatibility with the green body, making it difficult to exert a reinforcing effect; ordinary calcium-based bentonite has poor plasticity, which can easily lead to the green body drying and cracking, affecting the molding quality and increasing losses.

[0005] In summary, addressing the shortcomings of existing toilet ceramics such as unstable antibacterial properties, high-temperature deactivation, and insufficient strength, developing toilet ceramic materials and preparation methods that combine high-efficiency antibacterial properties, high strength, and stable molding is of significant practical importance and market value. Summary of the Invention

[0006] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide an antibacterial high-strength toilet ceramic material and its preparation method.

[0007] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides an antibacterial high-strength toilet ceramic material, which is composed of a body and a glaze layer; The green body comprises the following components by weight: 35-45 parts kaolin, 20-30 parts quartz, 15-25 parts feldspar, 5-10 parts composite modified nano alumina, 3-8 parts micron silicon carbide, 2-5 parts modified bentonite, 1-3 parts antibacterial agent, and 35-55 parts deionized water. The glaze layer comprises the following components in parts by weight: Feldspar 40-50 parts, quartz 20-30 parts, kaolin 5-10 parts, calcium carbonate 3-8 parts, antibacterial agent 2-5 parts, sintering aid 1-3 parts, and deionized water 35-60 parts; The micron-sized silicon carbide particles have a diameter of 3 μm; the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5.

[0008] The antibacterial agent is prepared by the following steps: Step a1: Add layered zirconium phosphate, anhydrous ethanol, and deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30-60 min at a power of 200-300W and a frequency of 40kHz. Then, stir with a magnetic stirrer at a stirring rate of 300-500r / min, add dilute nitric acid dropwise to adjust the pH value to 4-5, and continue stirring for 10-15 min. Add silver nitrate, zinc nitrate, and cerium nitrate, and continue stirring for 20-30 min. Then, transfer to a constant temperature water bath, heat to 65-75℃, and continue stirring for 4-8 h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake with distilled water until the pH value is neutral, and then place it in a forced-air drying oven at a temperature of 80-120℃ for 8-12 h. After that, grind and pass through a 200-mesh sieve to obtain silver-zinc-cerium zirconium phosphate antibacterial powder. Step a2: Add silver-zinc-cerium-zirconia phosphate antibacterial powder, anhydrous ethanol, and deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 20-30 min at a power of 200-300W and a frequency of 40kHz. Then, maintain a stirring rate of 300-400r / min, add boric acid and stir for 10-12 min. Then, while stirring, add tetraethyl orthosilicate dropwise, controlling the dropping rate to 1-2 drops / s. After the addition is complete, continue stirring for 30-60 min. Adjust the pH value to 8 with sodium hydroxide solution, adjust the temperature to 40-60℃, and continue stirring for 2-4 h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake 2-3 times with anhydrous ethanol, then wash with distilled water until neutral, and then place it in a forced-air drying oven and dry at a temperature of 80-100℃ for 6-8 h to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step a3: Spread the pre-coated silver-zinc-cerium-zirconium phosphate composite powder in an alumina crucible with a thickness of 2-5 mm. Place the alumina crucible in a muffle furnace, introduce air atmosphere at a rate of 50-100 mL / min, and heat from room temperature to 350-550℃ at a rate of 3-5℃ / min. Maintain constant temperature heat treatment for 1-3 hours. After heat treatment, allow it to cool naturally to room temperature, then grind it through a 200-mesh sieve to obtain the antibacterial agent.

[0009] In a preferred embodiment of the present invention, the ratio of the amount of layered zirconium phosphate, anhydrous ethanol, deionized water, silver nitrate, zinc nitrate and cerium nitrate used in step a1 is 100-110g: 200-300mL: 150-250mL: 0.8-1.5g: 12-25g: 1-3g.

[0010] In a preferred embodiment of the present invention, the concentration of the dilute nitric acid in step a1 is 1 mol / L.

[0011] In a preferred embodiment of the present invention, the ratio of silver-zinc-cerium-zirconium phosphate antibacterial powder, anhydrous ethanol, deionized water, boric acid and tetraethyl orthosilicate in step a2 is 100-110g: 150-250mL: 100-150mL: 2-5g: 8-15mL.

[0012] In a preferred embodiment of the present invention, the concentration of the sodium hydroxide solution in step a2 is 0.1 mol / L.

[0013] The composite modified nano-alumina is prepared by the following steps: Step b1: Add nano-alumina and deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30-40 min at a power of 300-400W and a frequency of 30kHz. Add yttrium nitrate, start a high-speed stirrer, and stir for 10-15 min at a speed of 1500-2000 r / min. Then adjust the pH value to 8-9 with dilute ammonia water and continue stirring for 1-1.5 h. After vacuum filtration, wash the filter cake with distilled water until the washing liquid is neutral. Then place it in a forced-air drying oven and dry for 8-10 h at a temperature of 80-100℃. Then place it in a muffle furnace and calcine at a heating rate of 3-5℃ / min to 600-650℃ for 2-3 h. Cool naturally to room temperature to obtain rare earth doped modified nano-alumina. Step b2: Add rare earth-doped modified nano-alumina, anhydrous ethanol, and deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30-40 minutes at a power of 300-400W and a frequency of 30kHz. Then adjust the stirring speed to 1500r / min and add γ-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 1-2 drops / s. After the addition is complete, adjust the pH value to 4-5 with dilute acetic acid, and continue stirring for 10-15 minutes. Then, the mixture is placed in a constant temperature water bath and stirred for 1-2 hours at a temperature of 50-70℃. After vacuum filtration, the filter cake is first washed 2-3 times with anhydrous ethanol, and then washed with deionized water until the washing liquid is neutral. The filter cake is then placed in a forced-air drying oven and dried for 6-8 hours at a temperature of 80-100℃. After that, it is placed in a muffle furnace and heated to 120-150℃ at a heating rate of 3-5℃ / min for 2-3 hours. It is then naturally cooled to room temperature to obtain composite modified nano-alumina.

[0014] In a preferred embodiment of the present invention, the ratio of nano-alumina, deionized water and yttrium nitrate in step b1 is 100-120g: 1000-1200mL: 1-2g.

[0015] In a preferred embodiment of the present invention, the mass fraction of the dilute ammonia water in step b1 is 25%.

[0016] In a preferred embodiment of the present invention, the particle size of the nano-alumina in step b1 is 50-100 nm.

[0017] In a preferred embodiment of the present invention, the ratio of rare earth-doped modified nano-alumina, anhydrous ethanol, deionized water and γ-aminopropyltriethoxysilane in step b2 is 100-120g: 750-900mL: 250-300mL: 2-6g.

[0018] In a preferred embodiment of the present invention, the mass fraction of the dilute acetic acid in step b2 is 10%.

[0019] The modified bentonite is prepared by the following steps: Ordinary calcium-based bentonite and deionized water are added to a beaker. A high-speed stirrer is started, and the speed is adjusted to 2000-2500 r / min. Stirring is carried out for 30-40 min to obtain a bentonite suspension. Carboxymethyl cellulose, polyacrylamide, and deionized water are added to the beaker and stirred with a glass rod for 15-20 min to obtain a composite modifier solution. The composite modifier solution is added dropwise to the bentonite suspension while stirring, with a speed of 2000-2500 r / min and a dropping rate of 1-2 drops / s. After the addition is complete, the beaker is placed in a constant temperature water bath and stirred for 1-2 h at a temperature of 60-80℃. Then, the mixture is vacuum filtered, and the filter cake is washed with distilled water until the washing liquid is neutral. Then, it is placed in a forced-air drying oven and dried for 8-10 h at a temperature of 80-100℃. Finally, it is placed in a universal pulverizer, pulverized, and passed through a 200-mesh sieve to obtain modified bentonite.

[0020] In a preferred embodiment of the present invention, the ratio of ordinary calcium-based bentonite, deionized water, carboxymethyl cellulose and polyacrylamide is 100-120g: 3200-3600mL: 2.5-3.0g: 1.5-1.8g.

[0021] In a preferred embodiment of the present invention, the polyacrylamide is BASF cationic polymer Zetag® 8165.

[0022] In a preferred embodiment of the present invention, the deionized water used in the preparation of the bentonite suspension accounts for 96% of the total amount; and the deionized water used in the preparation of the composite modifier solution accounts for 4% of the total amount.

[0023] Secondly, this application provides a method for preparing an antibacterial, high-strength toilet ceramic material, comprising the following steps: Step 1: Place kaolin, quartz, feldspar, composite modified nano alumina, micron-sized silicon carbide, modified bentonite, and antibacterial agent into a ball mill, add deionized water, and ball mill for 12-18 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 280-320 r / min. Then, place it in a vacuum pumice machine and pumice it 2-3 times under vacuum degree ≤-0.08MPa and temperature of 25-35℃. Use a slip casting process to make the mud blank into a toilet blank. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then, place it in a drying oven and dry it at a temperature of 80-120℃ for 4-6 hours to obtain a dried blank. Step 2: Place feldspar, quartz, kaolin, calcium carbonate, antibacterial agent and sintering aid into a ball mill, add deionized water, place in a planetary ball mill, ball-to-material ratio of 3:1, speed of 280-320 r / min, ball mill for 8-12 hours, after ball milling, let stand for 24-48 hours to obtain glaze slurry; Step 3: Using a spray glazing process, with a pressure of 0.4 MPa and a spraying distance of 25 cm, apply a glaze layer of 0.5 mm thickness to the surface of the dried body. After glazing, allow it to air dry naturally for 1.5 hours. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 950-1050℃ at a rate of 5-8℃ / min and hold for 3-4.5 hours. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere at a flow rate of 1.5 L / min and heat the body to 1200-1280℃ at a rate of 3-5℃ / min. Hold the body for 5-7 hours and then cool the body to below 500℃ at a rate of 2-3℃ / min. Allow the body to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0024] The beneficial effects of this invention are: This invention discloses an antibacterial high-strength toilet ceramic material and its preparation method. The method involves placing kaolin, quartz, feldspar, composite modified nano-alumina, micron-sized silicon carbide, modified bentonite, and an antibacterial agent into a ball mill and adding deionized water for ball milling. After vacuum kneading, the mixture is poured into a slurry and dried to obtain a dried green body. Feldspar, quartz, kaolin, calcium carbonate, the antibacterial agent, and a sintering aid are then placed into a ball mill and added to deionized water for ball milling. After settling, a glaze slurry is obtained. The dried green body is then sprayed with glaze and dried. Following low-temperature bisque firing, high-temperature sintering, and cooling, the antibacterial high-strength toilet ceramic material is obtained. The antibacterial agent enables the toilet ceramic to retain its properties even after high-temperature sintering. It boasts highly efficient, broad-spectrum, and long-lasting antibacterial properties, along with excellent compatibility with the ceramic matrix, high-temperature resistance, and no impact on material strength or glaze quality, truly achieving a synergistic integration of antibacterial and high-strength properties. The composite modified nano-alumina significantly enhances the density, flexural strength, and hardness of toilet ceramics, while maintaining uniform dispersion within the body and not affecting the activity of the antibacterial agent, achieving a synergistic compatibility between high strength and highly efficient antibacterial properties. Modified bentonite improves the plasticity, dry strength, and molding stability of the toilet ceramic body, reducing drying cracking, while also promoting uniform dispersion of antibacterial ions without affecting the high-temperature sintering performance and antibacterial effect of the ceramic, thus balancing moldability, high strength, and durable antibacterial properties.

[0025] In the preparation of antibacterial high-strength toilet ceramic material, an antibacterial agent is first prepared. Silver, zinc, and cerium ions enter the interlayer and surface of layered zirconium phosphate through ion exchange, forming a stable silver-zinc-cerium ternary metal-loaded zirconium phosphate structure, achieving uniform loading and fixation of multiple metal ions. Then, tetraethyl orthosilicate hydrolyzes under weakly alkaline conditions to generate silica. Boric acid, acting as a flux and coordination stabilizer, forms a uniform borosilicate oxide coating layer on the surface of the antibacterial powder, encapsulating the silver-zinc-cerium zirconium phosphate particles. Subsequently, low-temperature heat treatment dehydrates, condenses, and crystallizes the coating layer, forming a dense, high-temperature resistant silica-boron oxide composite. The process involves encapsulating a shell layer to obtain a structurally stable, slow-release, and controllable silver-zinc-cerium-zirconium phosphate-based composite antibacterial agent. Silver, zinc, and cerium ions are released slowly and stably through ion exchange and adsorption by the layered zirconium phosphate, avoiding burst release. This allows the agent to contact and disrupt the bacterial cell membrane, leading to leakage of intracellular substances and bacterial death. Furthermore, it binds to the sulfhydryl and amino groups of bacterial proteases, dehydrogenases, and respiratory enzymes, inactivating these enzymes and blocking bacterial metabolism, respiration, and replication. Simultaneously, the metal ions can enter the bacterial interior and bind to DNA and RNA, disrupting nucleic acid structures and inhibiting bacterial division and proliferation, thus achieving antibacterial effects. Additionally, Ce has Ce... 4+ / Ce 3+It has a variable valence state and can catalyze the generation of reactive oxygen species, oxidizing proteins and lipids within bacteria, causing oxidative damage and death of the bacteria. Furthermore, the silica-boron oxide inorganic coating on the outer layer of the antibacterial agent is heat-resistant and oxidation-resistant, ensuring that its antibacterial activity is not lost or decomposed after sintering ceramics at temperatures above 1200℃. Utilizing the synergistic effect of silver, zinc, and cerium metal ions, it significantly broadens the antibacterial spectrum, exhibiting highly efficient, rapid, and long-lasting bactericidal effects against common pathogens such as Escherichia coli and Staphylococcus aureus, with a high antibacterial rate. Using layered zirconium phosphate, which is chemically stable, non-toxic, and has no risk of dissolution, as a carrier, it can firmly bind metal ions, achieving slow release. This product offers long-lasting antibacterial protection, preventing rapid loss of metal ions and effectively extending the lifespan of the antibacterial agent. The silica-boron oxide coating formed on the surface of the antibacterial agent can withstand high-temperature sintering of ceramics, protecting the antibacterial active center from oxidation and deactivation. This successfully solves the problem of traditional antibacterial agents easily failing at high temperatures. Furthermore, the coated antibacterial agent particles are uniform and do not easily agglomerate, exhibiting good compatibility with the ceramic body and glaze. It does not produce pinholes, does not turn black, and does not affect the glaze gloss or ceramic strength. At the same time, this antibacterial agent does not leach heavy metals or release harmful substances, meeting the hygiene and safety requirements of sanitary ceramics. It is particularly suitable for products such as toilets and sanitary ware that come into long-term contact with the human body.

[0026] In the preparation of antibacterial high-strength toilet ceramic materials, a composite modified nano-alumina was prepared. Yttrium nitrate forms yttrium hydroxide under alkaline conditions and is uniformly attached to the surface of nano-alumina. After high-temperature calcination, yttrium oxide is doped into the alumina lattice, which can effectively inhibit the grain growth of nano-alumina during the high-temperature sintering process of ceramics, maintain the nano-reinforcing effect, and improve the high-temperature stability and interfacial bonding ability of alumina. γ-aminopropyltriethoxysilane undergoes hydrolysis under weak acid conditions and condenses with the hydroxyl groups on the surface of nano-alumina to form an organic coating layer, which significantly improves the dispersibility of nano-alumina, avoids agglomeration, and enhances its wettability and bonding strength with the ceramic body matrix. After composite modification, the nano-alumina is more uniformly dispersed in the body and the interfacial bonding is more dense, which can significantly improve the flexural strength, hardness, and impact resistance of the ceramic. At the same time, it has good compatibility with silver ions, zinc ions, and cerium ions in the system and does not affect the slow release and antibacterial activity of ternary metal ions, so that the ceramic material has high strength, high toughness, and efficient and long-lasting antibacterial properties.

[0027] In the preparation of antibacterial high-strength toilet ceramic materials, a modified bentonite was prepared. This modified bentonite involved organic intercalation and composite modification of ordinary calcium-based bentonite using carboxymethyl cellulose and polyacrylamide. The macromolecules of carboxymethyl cellulose and polyacrylamide could be inserted into the layered structure of bentonite, expanding the interlayer spacing and improving the dispersibility, suspension stability, and adsorption capacity of the bentonite. Simultaneously, a network structure was formed in the clay, significantly improving the plasticity and dry strength of the green body. During subsequent high-temperature sintering, the organic modified components could completely decompose and volatilize, leaving no impurities in the green body and not affecting the sintering quality of the ceramic. The bentonite enabled smoother green body forming, reduced cracking during drying, and improved the overall uniformity and density of the green body. It also exhibited good adsorption and dispersion effects on silver, zinc, and cerium ions in the system, enabling a more uniform distribution of antibacterial ions in the green body, preventing ion segregation, and ensuring a stable and long-lasting antibacterial effect. This resulted in ceramic materials possessing excellent forming and processing performance, high-strength mechanical properties, and highly efficient broad-spectrum antibacterial properties. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1:

[0030] This embodiment describes a method for preparing an antibacterial, high-strength toilet ceramic material, including the following steps: Step s1: Add 100g of layered zirconium phosphate, 200mL of anhydrous ethanol and 150mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 200W and a frequency of 40kHz. Then stir with a magnetic stirrer at a stirring rate of 300r / min, add 1mol / L dilute nitric acid to adjust the pH to 4, and continue stirring for 10min. Add 0.8g of silver nitrate, 12g of zinc nitrate and 1g of cerium nitrate, and continue stirring for 20min. Then transfer to a constant temperature water bath, heat to 65℃, and continue stirring for 4h. After the reaction is completed, cool to room temperature, then vacuum filter. Wash the filter cake with distilled water until the pH is neutral, and then place it in a forced-air drying oven and dry at 80℃ for 8h. After grinding, pass through a 200-mesh sieve to obtain silver-zinc-cerium zirconium phosphate antibacterial powder. Step s2: Add 100g of silver-zinc-cerium-zirconia phosphate antibacterial powder, 150mL of anhydrous ethanol and 100mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 20min at a power of 200W and a frequency of 40kHz. Then, keep the stirring speed at 300r / min, add 2g of boric acid and stir for 10min. Then, while stirring, add 8mL of tetraethyl orthosilicate dropwise, controlling the dropping rate to 1 drop / s. After the addition is complete, continue stirring for 30min. Adjust the pH value to 8 with 0.1mol / L sodium hydroxide solution, adjust the temperature to 40℃, and continue stirring for 2h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake twice with anhydrous ethanol, then wash it with distilled water until neutral, and then place it in a forced-air drying oven and dry it at a temperature of 80℃ for 6h to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step s3: Spread the pre-coated silver-zinc-cerium-zirconium phosphate composite powder in an alumina crucible with a thickness of 2 mm. Place the alumina crucible in a muffle furnace and introduce air at a rate of 50 mL / min. Heat the powder from room temperature to 350°C at a rate of 3°C / min and heat it at a constant temperature for 1 hour. After the heat treatment, allow it to cool naturally to room temperature. Then grind it through a 200-mesh sieve to obtain the antibacterial agent. Step s4: Add 100g of nano-alumina (particle size of nano-alumina is 50nm) and 1000mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 300W and a frequency of 30kHz. Add 1g of yttrium nitrate, start a high-speed stirrer, and stir for 10min at a speed of 1500r / min. Then adjust the pH value to 8 with 25% dilute ammonia water and continue stirring for 1h. After that, vacuum filter, wash the filter cake with distilled water until the washing liquid is neutral, and then put it in a forced-air drying oven and dry at a temperature of 80℃ for 8h. Then put it in a muffle furnace and heat it to 600℃ at a heating rate of 3℃ / min for 2h. Then cool it naturally to room temperature to obtain rare earth doped modified nano-alumina. Step s5: Add 100g of rare earth-doped modified nano-alumina, 750mL of anhydrous ethanol, and 250mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 300W and a frequency of 30kHz. Then adjust the stirring speed to 1500r / min, and add 2g of γ-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 1 drop / s. After the addition is complete, adjust the pH with 10% dilute acetic acid. When the H value reaches 4, continue stirring for 10 minutes. Then, place it in a constant temperature water bath and stir for 1 hour at 50°C. After vacuum filtration, wash the filter cake 2-3 times with anhydrous ethanol, then wash with deionized water until the washing liquid is neutral. Place the filter cake in a forced-air drying oven and dry it for 6 hours at 80°C. Then, place it in a muffle furnace and heat it to 120°C at a heating rate of 3°C / min for 2 hours. Allow it to cool naturally to room temperature to obtain composite modified nano-alumina. Step s6: Add 100g of ordinary calcium-based bentonite and 3072mL of deionized water to a beaker, start a high-speed stirrer, adjust the speed to 2000r / min, and stir for 30min to obtain a bentonite suspension. Add 2.5g of carboxymethyl cellulose and 1.5g of polyacrylamide (BASF cationic polymer Zetag®). 8165) and 128 mL of deionized water were added to a beaker and stirred with a glass rod for 15 min to obtain a composite modifier solution. The composite modifier solution was then added dropwise to the bentonite suspension while stirring at a speed of 2000 r / min and a dropping rate of 1 drop / s. After the addition was complete, the beaker was placed in a constant temperature water bath and stirred for 1 h at a temperature of 60℃. After that, the mixture was vacuum filtered and the filter cake was washed with distilled water until the washing liquid was neutral. Then, the mixture was placed in a forced-air drying oven and dried at a temperature of 80℃ for 8 h. After that, the mixture was placed in a universal pulverizer, pulverized, and passed through a 200-mesh sieve to obtain modified bentonite. Step s7: Place 35 parts kaolin, 20 parts quartz, 15 parts feldspar, 5 parts composite modified nano alumina, 3 parts micron-sized silicon carbide (micron-sized silicon carbide particle size is 3μm), 2 parts modified bentonite, and 1 part antibacterial agent into a ball mill, add 35 parts deionized water, and ball mill for 12 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 280 r / min. Then, put it into a vacuum pumice machine and pumice twice under the conditions of vacuum degree ≤-0.08MPa and temperature of 25℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then put it into a drying oven and dry it at a temperature of 80℃ for 4 hours to obtain a dried blank. Step s8: Place 40 parts feldspar, 20 parts quartz, 5 parts kaolin, 3 parts calcium carbonate, 2 parts antibacterial agent, and 1 part sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 35 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 280 r / min, and ball mill for 8 hours. After ball milling, let stand for 24 hours to obtain glaze slurry. Step s9: Using a spray glazing process, the pressure is 0.4MPa and the spraying distance is 25cm. Apply a glaze layer with glaze slurry to the surface of the dried body. The glaze layer thickness is 0.5mm. After glazing, allow it to air dry naturally for 1.5h. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 950℃ at a rate of 5℃ / min and hold for 3h. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere with a nitrogen flow rate of 1.5L / min. Heat the body to 1200℃ at a rate of 3℃ / min and hold for 5h. Then, cool the body to below 500℃ at a rate of 2℃ / min and allow it to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0031] Example 2:

[0032] This embodiment describes a method for preparing an antibacterial, high-strength toilet ceramic material, including the following steps: Step s1: Add 105g of layered zirconium phosphate, 250mL of anhydrous ethanol and 200mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 45min at a power of 250W and a frequency of 40kHz. Then stir with a magnetic stirrer at a stirring rate of 400r / min, add 1mol / L dilute nitric acid to adjust the pH to 4.5, and continue stirring for 13min. Add 1.2g of silver nitrate, 18g of zinc nitrate and 2g of cerium nitrate, and continue stirring for 25min. Then transfer to a constant temperature water bath, heat to 70℃, and continue stirring for 6h. After the reaction is completed, cool to room temperature, then vacuum filter, wash the filter cake with distilled water until the pH is neutral, and then place it in a forced-air drying oven at a temperature of 100℃ for 10h. After grinding, pass through a 200-mesh sieve to obtain silver zinc cerium zirconium phosphate antibacterial powder. Step s2: Add 105g of silver-zinc-cerium-zirconia phosphate antibacterial powder, 200mL of anhydrous ethanol and 130mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 25min at a power of 250W and a frequency of 40kHz. Then, while maintaining a stirring rate of 350r / min, add 3.5g of boric acid and stir for 11min. Then, while stirring, add 12mL of tetraethyl orthosilicate dropwise, controlling the dropping rate to 1 drop / s. After the addition is complete, continue stirring for 45min. Adjust the pH value to 8 with 0.1mol / L sodium hydroxide solution, adjust the temperature to 50℃, and continue stirring for 3h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake twice with anhydrous ethanol, then wash it with distilled water until neutral, and then place it in a forced-air drying oven and dry it at a temperature of 90℃ for 7h to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step s3: Spread the pre-coated silver-zinc-cerium-zirconium phosphate composite powder in an alumina crucible with a thickness of 3 mm. Place the alumina crucible in a muffle furnace, introduce air atmosphere at a rate of 75 mL / min, and heat from room temperature to 450°C at a rate of 4°C / min. Maintain the temperature for 2 hours. After the heat treatment, allow it to cool naturally to room temperature. Then grind it through a 200-mesh sieve to obtain the antibacterial agent. Step s4: Add 110g of nano-alumina (particle size of nano-alumina is 75nm) and 1100mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 35min at a power of 350W and a frequency of 30kHz. Add 1.5g of yttrium nitrate, start a high-speed stirrer, and stir for 13min at a speed of 1700r / min. Then adjust the pH value to 8.5 with 25% dilute ammonia water and continue stirring for 1.3h. After vacuum filtration, wash the filter cake with distilled water until the washing liquid is neutral. Then place it in a forced-air drying oven and dry at a temperature of 90℃ for 9h. Then place it in a muffle furnace and heat it to 630℃ at a heating rate of 4℃ / min for 2.5h. Let it cool naturally to room temperature to obtain rare earth doped modified nano-alumina. Step s5: Add 110g of rare earth-doped modified nano-alumina, 825mL of anhydrous ethanol, and 270mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 35min at a power of 350W and a frequency of 30kHz. Then, adjust the stirring speed to 1500r / min and add 4g of γ-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 1 drop / s. After the addition is complete, adjust the pH value with 10% dilute acetic acid. Continue stirring for 13 minutes until the temperature reaches 4.5. Then, place the mixture in a constant temperature water bath and stir for 1.5 hours at 60°C. After that, vacuum filter the mixture. First, wash the filter cake twice with anhydrous ethanol, then wash it with deionized water until the washing liquid is neutral. Place the filter cake in a forced-air drying oven and dry it for 7 hours at 90°C. Then, place it in a muffle furnace and heat it to 135°C at a heating rate of 4°C / min for 2.5 hours. Allow it to cool naturally to room temperature to obtain composite modified nano-alumina. Step s6: Add 110g of ordinary calcium-based bentonite and 3264mL of deionized water to a beaker, start a high-speed stirrer, adjust the speed to 2200r / min, and stir for 35min to obtain a bentonite suspension. Add 2.75g of carboxymethyl cellulose and 1.65g of polyacrylamide (BASF cationic polymer Zetag®). 8165) and 136 mL of deionized water were added to a beaker and stirred with a glass rod for 17 min to obtain a composite modifier solution. The composite modifier solution was then added dropwise to the bentonite suspension while stirring at a speed of 2200 r / min and a dropping rate of 1 drop / s. After the addition was complete, the beaker was placed in a constant temperature water bath and stirred for 1.5 h at a temperature of 70 ℃. After that, the mixture was vacuum filtered and the filter cake was washed with distilled water until the washing liquid was neutral. Then, it was placed in a forced-air drying oven and dried at a temperature of 90 ℃ for 9 h. After that, it was placed in a universal pulverizer, pulverized, and passed through a 200-mesh sieve to obtain modified bentonite. Step s7: Place 40 parts kaolin, 25 parts quartz, 20 parts feldspar, 7.5 parts composite modified nano alumina, 5.5 parts micron silicon carbide (micron silicon carbide particle size is 3μm), 3.5 parts modified bentonite, and 2 parts antibacterial agent into a ball mill, add 45 parts deionized water, and ball mill for 15 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 300 r / min. Then, put it into a vacuum pumice machine and pumice twice under vacuum degree ≤-0.08MPa and temperature of 30℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then put it into a drying oven and dry it at a temperature of 100℃ for 5 hours to obtain a dried blank. Step s8: Place 45 parts feldspar, 25 parts quartz, 7.5 parts kaolin, 5.5 parts calcium carbonate, 3.5 parts antibacterial agent, and 2 parts sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 47 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 300 r / min, and ball mill for 10 h. After ball milling, let stand for 26 h to obtain glaze slurry; Step s9: Using a spray glazing process, the pressure is 0.4MPa and the spraying distance is 25cm. Apply a glaze layer with glaze slurry to the surface of the dried body. The glaze layer thickness is 0.5mm. After glazing, allow it to air dry naturally for 1.5h. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 1000℃ at a rate of 6℃ / min and hold for 4h. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere with a nitrogen flow rate of 1.5L / min. Heat the body to 1240℃ at a rate of 4℃ / min and hold for 6h. Then, cool the body to below 500℃ at a rate of 2℃ / min and allow it to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0033] Example 3:

[0034] This embodiment describes a method for preparing an antibacterial, high-strength toilet ceramic material, including the following steps: Step s1: Add 110g of layered zirconium phosphate, 300mL of anhydrous ethanol and 250mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 60min at a power of 300W and a frequency of 40kHz. Then stir with a magnetic stirrer at a stirring rate of 500r / min, add 1mol / L dilute nitric acid to adjust the pH to 5, and continue stirring for 15min. Add 1.5g of silver nitrate, 25g of zinc nitrate and 3g of cerium nitrate, and continue stirring for 30min. Then transfer to a constant temperature water bath, heat to 75℃, and continue stirring for 8h. After the reaction is completed, cool to room temperature, then vacuum filter. Wash the filter cake with distilled water until the pH is neutral, and then place it in a forced-air drying oven at a temperature of 120℃ for 12h. After grinding, pass through a 200-mesh sieve to obtain silver-zinc-cerium zirconium phosphate antibacterial powder. Step s2: Add 110g of silver-zinc-cerium-zirconia phosphate antibacterial powder, 250mL of anhydrous ethanol and 150mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 300W and a frequency of 40kHz. Then, keep the stirring speed at 400r / min, add 5g of boric acid and stir for 12min. Then, while stirring, add 15mL of tetraethyl orthosilicate dropwise, controlling the dropping rate to 2 drops / s. After the addition is complete, continue stirring for 60min. Adjust the pH value to 8 with 0.1mol / L sodium hydroxide solution, adjust the temperature to 60℃, and continue stirring for 4h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake 3 times with anhydrous ethanol, then wash with distilled water until neutral, and then place it in a forced-air drying oven and dry at 100℃ for 8h to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step s3: Spread the pre-coated silver-zinc-cerium-zirconia phosphate composite powder in an alumina crucible with a thickness of 5 mm. Place the alumina crucible in a muffle furnace, introduce air atmosphere at a rate of 100 mL / min, and heat from room temperature to 550°C at a rate of 5°C / min. Maintain constant temperature heat treatment for 3 hours. After heat treatment, allow it to cool naturally to room temperature, then grind it through a 200-mesh sieve to obtain the antibacterial agent. Step s4: Add 120g of nano-alumina (particle size of nano-alumina is 100nm) and 1200mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 40min at a power of 400W and a frequency of 30kHz. Add 2g of yttrium nitrate, start a high-speed stirrer, and stir for 15min at a speed of 2000r / min. Then adjust the pH value to 9 with 25% dilute ammonia water and continue stirring for 1.5h. After vacuum filtration, wash the filter cake with distilled water until the washing liquid is neutral. Then place it in a forced-air drying oven and dry at a temperature of 100℃ for 10h. Then place it in a muffle furnace and heat it to 650℃ at a heating rate of 5℃ / min for 3h. Let it cool naturally to room temperature to obtain rare earth doped modified nano-alumina. Step s5: Add 120g of rare earth-doped modified nano-alumina, 900mL of anhydrous ethanol, and 300mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 40min at a power of 400W and a frequency of 30kHz. Then adjust the stirring speed to 1500r / min, and add 6g of γ-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 2 drops / s. After the addition is complete, adjust the mixture with 10% dilute acetic acid. The pH value was adjusted to 5, and stirring was continued for 15 minutes. Then, the mixture was placed in a constant temperature water bath and stirred at 70°C for 2 hours. After that, it was vacuum filtered. The filter cake was first washed three times with anhydrous ethanol, and then washed with deionized water until the washing liquid was neutral. The filter cake was placed in a forced-air drying oven and dried at 100°C for 8 hours. Then, it was placed in a muffle furnace and heated to 150°C at a heating rate of 5°C / min for 3 hours. After that, it was naturally cooled to room temperature to obtain composite modified nano alumina. Step s6: Add 120g of ordinary calcium-based bentonite and 3456mL of deionized water to a beaker, start a high-speed stirrer, adjust the speed to 2500r / min, and stir for 40min to obtain a bentonite suspension. Add 3.0g of carboxymethyl cellulose and 1.8g of polyacrylamide (BASF cationic polymer Zetag®). 8165) and 144 mL of deionized water were added to a beaker and stirred with a glass rod for 20 min to obtain a composite modifier solution. The composite modifier solution was then added dropwise to the bentonite suspension while stirring at a speed of 2500 r / min and a dropping rate of 2 drops / s. After the addition was complete, the beaker was placed in a constant temperature water bath and stirred for 2 h at a temperature of 80℃. After that, the mixture was vacuum filtered and the filter cake was washed with distilled water until the washing liquid was neutral. Then, the mixture was placed in a forced-air drying oven and dried at a temperature of 100℃ for 10 h. After that, the mixture was placed in a universal pulverizer, pulverized, and passed through a 200-mesh sieve to obtain modified bentonite. Step s7: Place 45 parts kaolin, 30 parts quartz, 25 parts feldspar, 10 parts composite modified nano alumina, 8 parts micron-sized silicon carbide (micron-sized silicon carbide particle size is 3μm), 5 parts modified bentonite, and 3 parts antibacterial agent into a ball mill, add 55 parts deionized water, and ball mill for 18 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 320 r / min. Then, put it into a vacuum pumice machine and pumice it 3 times under the conditions of vacuum degree ≤-0.08MPa and temperature of 35℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then put it into a drying oven and dry it at a temperature of 120℃ for 6 hours to obtain a dried blank. Step s8: Place 50 parts feldspar, 30 parts quartz, 10 parts kaolin, 8 parts calcium carbonate, 5 parts antibacterial agent, and 3 parts sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 60 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 320 r / min, and ball mill for 12 h. After ball milling, let stand for 48 h to obtain glaze slurry; Step s9: Using a spray glazing process, with a pressure of 0.4MPa and a spraying distance of 25cm, apply a glaze layer of 0.5mm thickness to the surface of the dried body. After glazing, allow it to air dry naturally for 1.5 hours. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 1050℃ at a rate of 8℃ / min and hold for 4.5 hours. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere at a flow rate of 1.5L / min and heat the body to 1280℃ at a rate of 5℃ / min. Hold the body for 7 hours and then cool the body to below 500℃ at a rate of 3℃ / min. Allow the body to cool naturally to room temperature to obtain an antibacterial high-strength toilet ceramic material.

[0035] Comparative Example 1: This comparative example illustrates a method for preparing an antibacterial, high-strength ceramic toilet material, comprising the following steps: Step s1: Add 100g of nano-alumina (particle size of nano-alumina is 50nm) and 1000mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 300W and a frequency of 30kHz. Add 1g of yttrium nitrate, start a high-speed stirrer, and stir for 10min at a speed of 1500r / min. Then adjust the pH value to 8 with 25% dilute ammonia water and continue stirring for 1h. After that, vacuum filter, wash the filter cake with distilled water until the washing liquid is neutral, and then put it in a forced-air drying oven and dry it at a temperature of 80℃ for 8h. Then put it in a muffle furnace and heat it to 600℃ at a heating rate of 3℃ / min for 2h. Then cool it naturally to room temperature to obtain rare earth doped modified nano-alumina. Step s2: Add 100g of rare earth-doped modified nano-alumina, 750mL of anhydrous ethanol, and 250mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 300W and a frequency of 30kHz. Then adjust the stirring speed to 1500r / min, and add 2g of γ-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 1 drop / s. After the addition is complete, adjust the pH with 10% dilute acetic acid. When the H value reaches 4, continue stirring for 10 minutes. Then, place it in a constant temperature water bath and stir for 1 hour at 50°C. After vacuum filtration, wash the filter cake 2-3 times with anhydrous ethanol, then wash with deionized water until the washing liquid is neutral. Place the filter cake in a forced-air drying oven and dry it for 6 hours at 80°C. Then, place it in a muffle furnace and heat it to 120°C at a heating rate of 3°C / min for 2 hours. Allow it to cool naturally to room temperature to obtain composite modified nano-alumina. Step s3: Add 100g of ordinary calcium-based bentonite and 3072mL of deionized water to a beaker, start a high-speed stirrer, adjust the speed to 2000r / min, and stir for 30min to obtain a bentonite suspension. Add 2.5g of carboxymethyl cellulose and 1.5g of polyacrylamide (BASF cationic polymer Zetag®). 8165) and 128 mL of deionized water were added to a beaker and stirred with a glass rod for 15 min to obtain a composite modifier solution. The composite modifier solution was then added dropwise to the bentonite suspension while stirring at a speed of 2000 r / min and a dropping rate of 1 drop / s. After the addition was complete, the beaker was placed in a constant temperature water bath and stirred for 1 h at a temperature of 60℃. After that, the mixture was vacuum filtered and the filter cake was washed with distilled water until the washing liquid was neutral. Then, the mixture was placed in a forced-air drying oven and dried at a temperature of 80℃ for 8 h. After that, the mixture was placed in a universal pulverizer, pulverized, and passed through a 200-mesh sieve to obtain modified bentonite. Step s4: Place 35 parts kaolin, 20 parts quartz, 15 parts feldspar, 5 parts composite modified nano alumina, 3 parts micron-sized silicon carbide (micron-sized silicon carbide particle size is 3μm) and 2 parts modified bentonite into a ball mill, add 35 parts deionized water, and ball mill for 12 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 280 r / min. Then, put it into a vacuum pumice machine and pumice twice under the conditions of vacuum degree ≤-0.08MPa and temperature of 25℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then put it into a drying oven and dry it at a temperature of 80℃ for 4 hours to obtain the dried blank. Step s5: Place 40 parts feldspar, 20 parts quartz, 5 parts kaolin, 3 parts calcium carbonate, and 1 part sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 35 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 280 r / min, and ball mill for 8 hours. After ball milling, let stand for 24 hours to obtain the glaze slurry. Step s6: Using a spray glazing process, the pressure is 0.4MPa and the spraying distance is 25cm. Apply a glaze layer with glaze slurry to the surface of the dried body. The glaze layer thickness is 0.5mm. After glazing, allow it to air dry naturally for 1.5h. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 950℃ at a rate of 5℃ / min and hold for 3h. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere with a nitrogen flow rate of 1.5L / min. Heat the body to 1200℃ at a rate of 3℃ / min and hold for 5h. Then, cool the body to below 500℃ at a rate of 2℃ / min and allow it to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0036] Comparative Example 2: This comparative example illustrates a method for preparing an antibacterial, high-strength ceramic toilet material, comprising the following steps: Step s1: Add 100g of layered zirconium phosphate, 200mL of anhydrous ethanol and 150mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 30min at a power of 200W and a frequency of 40kHz. Then stir with a magnetic stirrer at a stirring rate of 300r / min, add 1mol / L dilute nitric acid to adjust the pH to 4, and continue stirring for 10min. Add 0.8g of silver nitrate, 12g of zinc nitrate and 1g of cerium nitrate, and continue stirring for 20min. Then transfer to a constant temperature water bath, heat to 65℃, and continue stirring for 4h. After the reaction is completed, cool to room temperature, then vacuum filter. Wash the filter cake with distilled water until the pH is neutral, and then place it in a forced-air drying oven and dry at 80℃ for 8h. After grinding, pass through a 200-mesh sieve to obtain silver-zinc-cerium zirconium phosphate antibacterial powder. Step s2: Add 100g of silver-zinc-cerium-zirconia phosphate antibacterial powder, 150mL of anhydrous ethanol and 100mL of deionized water to a beaker, place it in an ultrasonic disperser, and ultrasonically disperse for 20min at a power of 200W and a frequency of 40kHz. Then, keep the stirring speed at 300r / min, add 2g of boric acid and stir for 10min. Then, while stirring, add 8mL of tetraethyl orthosilicate dropwise, controlling the dropping rate to 1 drop / s. After the addition is complete, continue stirring for 30min. Adjust the pH value to 8 with 0.1mol / L sodium hydroxide solution, adjust the temperature to 40℃, and continue stirring for 2h. After the reaction is complete, cool to room temperature, then vacuum filter. Wash the filter cake twice with anhydrous ethanol, then wash it with distilled water until neutral, and then place it in a forced-air drying oven and dry it at a temperature of 80℃ for 6h to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step s3: Spread the pre-coated silver-zinc-cerium-zirconium phosphate composite powder in an alumina crucible with a thickness of 2 mm. Place the alumina crucible in a muffle furnace and introduce air at a rate of 50 mL / min. Heat the powder from room temperature to 350°C at a rate of 3°C / min and heat it at a constant temperature for 1 hour. After the heat treatment, allow it to cool naturally to room temperature. Then grind it through a 200-mesh sieve to obtain the antibacterial agent. Step s4: Place 35 parts kaolin, 20 parts quartz, 15 parts feldspar, 5 parts nano alumina (nano alumina particle size of 50nm), 3 parts micron silicon carbide (micron silicon carbide particle size of 3μm), 2 parts ordinary calcium-based bentonite, and 1 part antibacterial agent into a ball mill, add 35 parts deionized water, and ball mill for 12 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 280r / min. Then, place it in a vacuum pumice machine and pumice twice under vacuum degree ≤-0.08MPa and temperature of 25℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then place it in a drying oven and dry it at a temperature of 80℃ for 4 hours to obtain a dried blank. Step s5: Place 40 parts feldspar, 20 parts quartz, 5 parts kaolin, 3 parts calcium carbonate, 2 parts antibacterial agent, and 1 part sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 35 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 280 r / min, and ball mill for 8 hours. After ball milling, let stand for 24 hours to obtain glaze slurry. Step s6: Using a spray glazing process, the pressure is 0.4MPa and the spraying distance is 25cm. Apply a glaze layer with glaze slurry to the surface of the dried body. The glaze layer thickness is 0.5mm. After glazing, allow it to air dry naturally for 1.5h. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 950℃ at a rate of 5℃ / min and hold for 3h. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere with a nitrogen flow rate of 1.5L / min. Heat the body to 1200℃ at a rate of 3℃ / min and hold for 5h. Then, cool the body to below 500℃ at a rate of 2℃ / min and allow it to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0037] Comparative Example 3: This comparative example illustrates a method for preparing an antibacterial, high-strength ceramic toilet material, comprising the following steps: Step s1: Place 35 parts kaolin, 20 parts quartz, 15 parts feldspar, 5 parts nano alumina (nano alumina particle size of 50nm), 3 parts micron silicon carbide (micron silicon carbide particle size of 3μm), and 2 parts ordinary calcium-based bentonite into a ball mill, add 35 parts deionized water, and ball mill for 12 hours. The ball milling media is zirconia beads, the ball-to-material ratio is 3:1, and the rotation speed is 280r / min. Then, place it in a vacuum pumice machine and pumice twice under vacuum degree ≤-0.08MPa and temperature of 25℃. Use the slip casting process to make the pumice into toilet blanks. After molding, place it in a ventilated place to dry naturally until the moisture content of the blank is ≤8%. Then place it in a drying oven and dry it at a temperature of 80℃ for 4 hours to obtain a dried blank. Step s2: Place 40 parts feldspar, 20 parts quartz, 5 parts kaolin, 3 parts calcium carbonate, and 1 part sintering aid (the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5) into a ball mill, add 35 parts deionized water, place in a planetary ball mill, with a ball-to-material ratio of 3:1, a rotation speed of 280 r / min, and ball mill for 8 hours. After ball milling, let stand for 24 hours to obtain the glaze slurry. Step s3: Using a spray glazing process, the pressure is 0.4MPa and the spraying distance is 25cm. Apply a glaze layer with glaze slurry to the surface of the dried body. The glaze layer thickness is 0.5mm. After glazing, allow it to air dry naturally for 1.5h. Then, place the glazed body into a sintering furnace for low-temperature bisque firing. Heat the body to 950℃ at a rate of 5℃ / min and hold for 3h. Cool the body to room temperature in the furnace and place it back into the sintering furnace for high-temperature sintering. Introduce a nitrogen atmosphere with a nitrogen flow rate of 1.5L / min. Heat the body to 1200℃ at a rate of 3℃ / min and hold for 5h. Then, cool the body to below 500℃ at a rate of 2℃ / min and allow it to cool naturally to room temperature to obtain antibacterial high-strength toilet ceramic material.

[0038] Performance testing: The antibacterial high-strength toilet ceramic materials of Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; Bending strength test: The test was conducted in accordance with GB / T 3810.4-2016 "Test methods for ceramic tiles - Part 4: Determination of modulus of rupture and breaking strength". The three-point bending method was used. The sample size was 80mm×10mm×5mm, the span was 60mm, the loading rate was 0.5mm / min, and the average value of 5 groups of samples was taken.

[0039] Water absorption test: The test was conducted in accordance with GB / T 3810.3-2016 "Test methods for ceramic tiles - Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density". The boiling method was used to test the water absorption rate and calculate the mass change of the sample before and after water absorption. The average value was then taken.

[0040] Drying crack rate test: Take 30 blank samples of the same size and the same process, dry them naturally until the moisture content is ≤8%, and then dry them at 80℃ for 4 hours. Count the number of samples with obvious drying cracks and calculate the drying crack rate.

[0041] Antibacterial performance test: The test was conducted in accordance with JC / T 897-2014 "Antibacterial properties of antibacterial ceramic products" using the shaking flask method. Escherichia coli and Staphylococcus aureus were selected as test strains, and the antibacterial rate was calculated.

[0042] High-temperature antibacterial stability test: After the ceramic sample was sintered at 1200℃, the antibacterial performance test was repeated according to the above method. The change in antibacterial rate before and after sintering was compared to verify the high-temperature stability of the antibacterial agent.

[0043] The test results are shown in Table 1: Table 1: Test Results Summary Table

[0044] Referring to Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the antibacterial high-strength toilet ceramic material has excellent high-efficiency antibacterial properties, high strength characteristics, stable molding properties, and excellent comprehensive properties.

[0045] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0046] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength antibacterial ceramic material for toilets, characterized in that, It consists of a body and a glaze layer; The green body comprises the following components by weight: 35-45 parts kaolin, 20-30 parts quartz, 15-25 parts feldspar, 5-10 parts composite modified nano alumina, 3-8 parts micron silicon carbide, 2-5 parts modified bentonite, 1-3 parts antibacterial agent, and 35-55 parts deionized water. The glaze layer comprises the following components in parts by weight: Feldspar 40-50 parts, quartz 20-30 parts, kaolin 5-10 parts, calcium carbonate 3-8 parts, antibacterial agent 2-5 parts, sintering aid 1-3 parts, and deionized water 35-60 parts; The micron-sized silicon carbide particles have a diameter of 3 μm; the sintering aid is a samarium fluoride-yttrium fluoride composite aid, with a mass ratio of samarium fluoride to yttrium fluoride of 1:1.5; The antibacterial agent is prepared by the following steps: Step a1: The layered zirconium phosphate, anhydrous ethanol and deionized water are ultrasonically dispersed, then stirred, the pH value is adjusted, and stirring is continued. Silver nitrate, zinc nitrate and cerium nitrate are added and stirring is continued. After cooling, vacuum filtration is performed, followed by washing, drying, grinding and sieving to obtain silver zinc cerium zirconium phosphate antibacterial powder. Step a2: Disperse the silver-zinc-cerium-zirconia phosphate antibacterial powder, anhydrous ethanol and deionized water by ultrasonication, add boric acid and stir, then add tetraethyl orthosilicate, continue stirring, adjust the pH value, continue stirring, cool, then vacuum filter, wash, and then dry to obtain pre-coated silver-zinc-cerium-zirconia phosphate composite powder. Step a3: Place the pre-coated silver-zinc-cerium-zirconium phosphate composite powder into a muffle furnace, heat treat it, cool it, and then grind and sieve it to obtain the antibacterial agent.

2. The antibacterial high-strength toilet ceramic material according to claim 1, characterized in that, The ratio of the amount of layered zirconium phosphate, anhydrous ethanol, deionized water, silver nitrate, zinc nitrate and cerium nitrate used in step a1 is 100-110g: 200-300mL: 150-250mL: 0.8-1.5g: 12-25g: 1-3g.

3. The antibacterial high-strength toilet ceramic material according to claim 1, characterized in that, The ratio of silver-zinc-cerium-zirconium phosphate antibacterial powder, anhydrous ethanol, deionized water, boric acid, and tetraethyl orthosilicate in step a2 is 100-110g: 150-250mL: 100-150mL: 2-5g: 8-15mL.

4. The antibacterial high-strength toilet ceramic material according to claim 1, characterized in that, The composite modified nano-alumina was prepared by the following steps: Step b1: Disperse nano-alumina and deionized water by ultrasonication, add yttrium nitrate and stir, then adjust the pH value, continue stirring, then vacuum filter, wash, then dry, then calcine and cool to obtain rare earth doped modified nano-alumina. Step b2: Rare earth-doped modified nano-alumina, anhydrous ethanol and deionized water are ultrasonically dispersed, then γ-aminopropyltriethoxysilane is added, the pH value is adjusted, stirring is continued, then vacuum filtration is performed, followed by washing and drying, and then heat treatment is carried out in a muffle furnace and cooled to obtain composite modified nano-alumina.

5. The antibacterial high-strength toilet ceramic material according to claim 4, characterized in that, In step b1, the ratio of nano-alumina, deionized water, and yttrium nitrate is 100-120g: 1000-1200mL: 1-2g; the particle size of the nano-alumina is 50-100nm.

6. The antibacterial high-strength toilet ceramic material according to claim 4, characterized in that, In step b2, the ratio of rare earth-doped modified nano-alumina, anhydrous ethanol, deionized water, and γ-aminopropyltriethoxysilane is 100-120g: 750-900mL: 250-300mL: 2-6g.

7. The antibacterial high-strength toilet ceramic material according to claim 1, characterized in that, The modified bentonite is prepared by the following steps: Ordinary calcium-based bentonite and deionized water were added to a beaker and stirred to obtain a bentonite suspension. Carboxymethyl cellulose, polyacrylamide, and deionized water were added to the beaker and stirred to obtain a composite modifier solution. The composite modifier solution was added dropwise to the bentonite suspension and stirred continuously. Then, the mixture was vacuum filtered, washed, dried, and pulverized to obtain modified bentonite.

8. The antibacterial high-strength toilet ceramic material according to claim 7, characterized in that, The ratio of ordinary calcium-based bentonite, deionized water, carboxymethyl cellulose, and polyacrylamide is 100-120g: 3200-3600mL: 2.5-3.0g: 1.5-1.8g; the deionized water used in the preparation of the bentonite suspension accounts for 96% of the total amount; and the deionized water used in the preparation of the composite modifier solution accounts for 4% of the total amount.

9. A method for preparing an antibacterial, high-strength toilet ceramic material, characterized in that, The preparation of the antibacterial high-strength toilet ceramic material as described in any one of claims 1-8 includes the following steps: Step 1: Put kaolin, quartz, feldspar, composite modified nano alumina, micron silicon carbide, modified bentonite and antibacterial agent into a ball mill, add deionized water, ball mill, then put into a vacuum mud kneading machine to knead mud, use slip casting molding process to make the mud blank into toilet blank, let it dry naturally in a ventilated place, and then dry it again to obtain a dried blank. Step 2: Place feldspar, quartz, kaolin, calcium carbonate, antibacterial agent and sintering aid into a ball mill, add deionized water, place in a planetary ball mill for ball milling, let stand, and obtain glaze slurry; Step 3: Using a spray glazing process, apply a glaze layer to the surface of the dried body with glaze slurry, let it air dry naturally, and then put the glazed body into a sintering furnace for low-temperature bisque firing, cooling, and then high-temperature sintering. After cooling, the antibacterial high-strength toilet ceramic material is obtained.